FRI0197 EFFICACY DATA OF MC2–03 (CICLOSPORIN 0.03% AND 0.06% EYEDROPS) IN SJOGREN'S PATIENTS WITH SEVERE KERATITIS: OUTCOMES OF THE NORTHERN LIGHTS PHASE 2B TRIAL. (June 2019) - Gomez, Frederic; Selmer, Johan; Præstegaard, Morten; Teus, Miguel; Pablo, Luis; Maza, Maite Sainz de la; Heegaard, Steffen
Abstract : Background: Sjögren's syndrome is one of the most common rheumatic autoimmune disorders (1). It is a chronic systemic autoimmune disease in which immunomediated inflammation, characterized by lymphocytic infiltration of exocrine glands and epithelia, causes secretory gland dysfunction leading to dryness of the main mucosal surfaces (2) including dry eye with severe keratitis. Ciclosporin is a well-known immunosuppressant with anti-inflammatory properties through inhibition of cell-mediated reactions (inhibit the release of cytokines including IL-2). Objectives: To report the clinical efficacy of MC2-03 (ciclosporin 0.03% and 0.06% eyedrops) in Sjogren's patients with severe keratitis from a 6-month clinical trial. Methods: The NORTHERN LIGHTS trial is a randomized, double masked, controlled multicentre European trial that assessed MC2-03 0.03%, MC2-03 0.06%, vehicle and best-standard-of-care (BSC) for the treatment of moderate-to-severe dry eye disease (patients having baseline corneal fluorescein staining (CFS) score 3 or 4). The full analysis set consisted of a total of 255 patients with 66 patients having a documented history of Sjögren's syndrome. The objective of the trial was to evaluate safety and efficacy of MC2-03 after treatment once daily for 6 months followed by a 3 month safety follow-up. The primary efficacy endpoint was the proportion of patients achieving 2-grade improvement in CFS. CFS was evaluated using the modified Oxford grading system: a 7-point ordinal scale (0, 0.5, and 1 to 5), where grade 0 represents complete corneal clearing (absence of staining dots). Results: The 66 patients with documented history of Sjögren's syndrome constituted 25.9% of the trial population with 90.9% of the patients being females (n=60). Among the Sjögren patients, 58% (n=38) had severe dry eye (CFS 4) at baseline. Data analyzed for observed cases showed that the proportion of Sjogren's patients achieving 2-grade improvement of CFS (baseline CFS 3 and CFS 4) was higher in MC2-03 groups compared to the control groups (Table 1 ). When patients treated with any active were compared to patients treated with any control, a 2-grade improvement of the CFS was observed in 51.9% patients in the combined active group vs. 26.7% for the combined control group (p=0.0620). Using the same approach, the most severe patients, having CFS 4 at baseline, had a statistically significantly higher responder rate of 64.3% in the combined active group versus 21.1% in the combined control group (p=0.0286). Conclusion: Data from the NORTHERN LIGHTS trial show that MC2-03 ciclosporin eyedrops has the potential to be a safe, well-tolerated and efficient treatment in Sjogren's patients. References: [1] Fox, et al. 2000 [2] Kassan, et al. 2004 Disclosure of Interests: Frederic Gomez Employee of: MC2 Therapeutics, Johan Selmer Employee of: MC2 Therapeutics, Morten Præstegaard Employee of: MC2 Therapeutics, Miguel Teus Grant/research support from: Alcon, Allergan, Novartis, Johnson & Johnson, Consultant for: Alcon, Allergan, Novartis, Johnson & Johnson, Santen, Speakers bureau: Alcon, Allergan, Johnson & Johnson, Luis Pablo Consultant for: Alcon, Allergan, Santen, MSD, Speakers bureau: Alcon, Allergan, Santen, Thea, MSD, Maite Sainz de la Maza Consultant for: Abbvie, Dompe, Santen, Speakers bureau: Bausch & Lomb, Brill, Esteve, Santen, Thea, Steffen Heegaard Speakers bureau: Alcon, Santen, Thea